Hardness Tests and Dimensional and Shape Precision Analysis of Construction and Agricultural Machinery Components - Kvasnová, Petra; Kučerka, Martin; Hrubý, Dušan; Novák, Daniel; Novák, Viktor (Manufacturing Technology Journal, 2018)
The article deals with hardness tests and dimensional and shape precision analysis of construction and agricultural machinery components, namely with the clamping head and case of hydraulic hammer. The clamping head is made of 41 4220 class (1.7131, 16MnCr5) construction stainless steel and the case is made of 41 5130 class (1.7218, 25CrMo4) construction stainless steel. The micro hardness was measured on VICKERS LM 700 AT hardness tester, according to the national standard STN EN ISO 6507-1: this procedure includes injection of a diamond regular four-bladed pyramid with a 136° peak angle into the tested material with following parameters: objective lens X50, load 10 N, indentation time 10 s. The average HV micro hardness value was determined from 10 measuring points (distances) on 70 samples of the hydraulic hammer case and from 10 measuring points (distances) on 200 samples of the hydraulic hammer clamping head. To measure dimensional and shape accuracy, Perthometer MAHR, equipped with PCV 350 slider unit with sensors with 350 mm length range and a mobile 6-axis 3D measuring arm Romer Absolute Arm 7535 with a working range of 3.5 m were used. This way, basic contour elements were determined: radii, distances and angles. Using the mobile 3D measuring arm, the tolerances of circularity, coaxiallity and perpendicularity were also measured. Technical drawings, contourrograph measuring protocols and tables of dimensional and shape precision deviations are listed in the conclusion of the article.
Keywords: Hardness tests; dimensional and shape precision analysis; construction stainless steel; production engineering; construction and agricultural machines